2012
DOI: 10.1037/a0028632
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic alliance and treatment outcome in the primary care behavioral health model.

Abstract: The current study investigated therapeutic alliance and clinical improvement within an integrated primary care behavioral health model. Participants included 542 primary care patients seen in two large family medicine clinics. Mental health symptoms and functioning were assessed using the 20-item Behavioral Health Measure (Kopta & Lowery, 2002) at the beginning of each patient appointment. Therapeutic alliance was measured with the Therapeutic Bond Scale (CelestHealth Solutions, 2008) following an initial appo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
41
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 81 publications
8
41
0
Order By: Relevance
“…With regard to therapeutic alliance, contrary to our expectations, we found Latino patients endorsed higher therapeutic alliance compared to non-Latino Whites, and both groups showed high alliance. This is also comparable to other research on alliance in IBHC models (Corso et al, 2012). …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…With regard to therapeutic alliance, contrary to our expectations, we found Latino patients endorsed higher therapeutic alliance compared to non-Latino Whites, and both groups showed high alliance. This is also comparable to other research on alliance in IBHC models (Corso et al, 2012). …”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our follow-up rates were similar to those found in other IBHC models (Bryan et al, 2012; Corso et al, 2012). In particular, we found that approximately 28.0% of Latino patients and 34.7% of non-Latino White patients attended their scheduled follow-up sessions, which is similar to the 29.8% attendance rate found by Bryan and colleagues (2012) and the 28.4% found in Corso and colleagues (2012).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Medical providers will typically introduce BHCs using a “warm-handoff” that includes a brief description of presenting concerns and the role of the BHC on the medical team. BHCs tend to use brief assessment/screening tools and adapted versions of evidence-based interventions or intervention components, in particular, strategies and techniques based on cognitive–behavioral principles (Bridges et al, 2013; Bryan et al, 2012; Corso et al, 2012; Hunter, Goodie, Oordt, & Dobmeyer, 2009; Ray-Sannerud et al, 2012). …”
Section: Brief Introduction To Ibhc and Outcome Researchmentioning
confidence: 99%
“…Preliminary findings estimate that a majority of patients—just over 70%—experience significant improvement when treated in IBHC settings (Bridges et al, 2013; Bryan et al, 2012; Corso et al, 2012). Patients with more severe initial impairment tend to improve more rapidly than patients with less severe initial impairment.…”
Section: Brief Introduction To Ibhc and Outcome Researchmentioning
confidence: 99%